RELIGIOUS MODERATION: BADUY MUALAF COMMUNNITY: STUDY OF LIVING RELIGIOUS MODERATION IN KOMPOL LEUWIDAMAR VILLAGE, LEBAK-BANTEN - Mulyadi, Yadi (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2022)
This study is a field study to find out more about the cultural practice of religious moderation in the Bedouin convert community in Kompol Leuwidamar Village, Lebak Banten, which has lived for hundreds of years. The method used in this research is a qualitative method which is a field research. This is an attempt to obtain valid and intact data regarding religious moderation in the view of the Baduy Muslim Converts Community in Kompol Village. The data collection techniques are carried out by means of observation, interviews, and documentation. The values ??of religious moderation (national commitment, tolerance, non-violence, and cultural accommodative) in the Baduy convert community in Kompol village were already practiced before the government had a strategic study on 'Religious Moderation'. They have been practicing mutual cooperation, mutual help, dialogue, tolerance, and being adaptive to foreign cultures since hundreds of centuries ago, even before they became converts, the practice of religious moderation had become a way of life everyday, consciously or unconsciously. . Even though there has actually been a shift in cultural values, the Mualaf Community is able to live side by side with the Inner Baduy